Relationship of physical fitness profile and the number of technical error at the stages of ski training among high class skiers with different training load structures - Lebedev M.M. ,; Popkova A.B. ,; Myakinchenko E.B. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess the relationship between the profile of physical fitness and the number of technical errors made when passing training routes at the stages of ski training by high-class skiers who have a different structure of training loads at the stage of physical training. Methods and structure of the study. Loads during two macrocycles (104 weeks) in eight adult men and five women of different ski specializations for 84 indicators were recorded daily. Testing was carried out according to the program of staged examinations of Russian national teams on 91 indicators - in May, July and October. Results and conclusions. In the group of alpine skiers with a larger proportion (p<0.05) of low- and high-intensity aerobic exercise, but a smaller proportion of glycolytic-oriented means, athletes had better VO2max and anaerobic threshold indicators, while they made fewer technical errors when passing training routes, especially during the second half of the ski training stage. High aerobic performance may be one of the factors that increases the efficiency of technical training by skiers in conditions of accumulation of fatigue during daily training sessions at the stage of ski training.